Identification of the Adult Hematopoietic Liver as the Primary Reservoir for the Recruitment of Pro-regenerative Macrophages Required for Salamander Limb Regeneration - Debuque, Ryan J.; Hart, Andrew J.; Johnson, Gabriela H.; Rosenthal, Nadia A.; Godwin, James W. (Frontiers in Cell and Developmental Biology, 2021)
The lack of scar-free healing and regeneration in many adult human tissues imposes severe limitations on the recovery of function after injury. In stark contrast, salamanders can functionally repair a range of clinically relevant tissues throughout adult life. The impressive ability to regenerate whole limbs after amputation, or regenerate following cardiac injury, is critically dependent on the recruitment of (myeloid) macrophage white blood cells to the site of injury. Amputation in the absence of macrophages results in regeneration failure and scar tissue induction. Identifying the exact hematopoietic source or reservoir of myeloid cells supporting regeneration is a necessary step in characterizing differences in macrophage phenotypes regulating scarring or regeneration across species. Mammalian wounds are dominated by splenic-derived monocytes that originate in the bone marrow and differentiate into macrophages within the wound. Unlike mammals, adult axolotls do not have functional bone marrow but instead utilize liver and spleen tissues as major sites for adult hematopoiesis. To interrogate leukocyte identity, tissue origins, and modes of recruitment, we established several transgenic axolotl hematopoietic tissue transplant models and flow cytometry protocols to study cell migration and identify the source of pro-regenerative macrophages. We identified that although bidirectional trafficking of leukocytes can occur between spleen and liver tissues, the liver is the major source of leukocytes recruited to regenerating limbs. Recruitment of leukocytes and limb regeneration occurs in the absence of the spleen, thus confirming the dependence of liver derived myeloid cells in regeneration and that splenic maturation is dispensable for the education of pro-regenerative macrophages. This work provides an important foundation for understanding the hematopoietic origins and education of myeloid cells recruited to, and essential for, adult tissue regeneration.